Injectable HAMA-CPC hydrogels loaded with high-yield 3D bioprinted adipose-derived stem cell small extracellular vesicles for increased bone repair - Wenbin Xu; Wenling Gao; Yi Zhang; Gang Hou; Wenhui Zhang; Jintao Deng; Kun Wang; Yichun Xu; Boxun Liu; Tao Xu; Chang Liu; Tangzhao Liang (Journal of Nanobiotechnology)
Abstract In the field of bone tissue engineering, the development of effective strategies for bone defect repair remains a major challenge. Herein, we report a novel approach involving the integration of high-yield 3D bioprinted adipose-derived stem cell small extracellular vesicles (3D-sEVs) into an injectable HAMA-CPC hydrogel (HAMA-CPC@3D-sEVs). In vitro, HAMA-CPC@3D-sEVs significantly promoted the proliferation, migration, and osteogenic differentiation of bone marrow stromal cells (BMSCs) and promoted angiogenesis in human umbilical vein endothelial cells (HUVECs). In vivo, in a rat tibial defect model, this treatment strongly promoted bone regeneration, increasing the bone volume fraction (BV/TV), bone volume (BV), and trabecular thickness (Tb.Th) at 4 weeks post-surgery. Mechanistically, proteomic analysis revealed that NAMPT in 3D-sEVs upregulated S1PR1 in HUVECs, leading to increased VEGF expression and angiogenesis. These findings suggest that 3D-sEVs-functionalized HAMA-CPC hydrogels have good potential for bone defect repair. Graphical abstract Schematic diagram of the overall study design of HAMA-CPC@3D-sEVs for the bone regeneration in rat